RED GINGER INSTANT POWDER PROCESSING - Rahmaniza, Rahmaniza; Astuti, Epu Margi; Nadia, Fatma (LPPM Univ. Ibn Khaldun Bogor, 2025)
Red ginger (Zingiber officinale var. rubrum) is widely known as a traditional medicinal plant with various health benefits, including anti-inflammatory, antimicrobial, and antioxidants. However, its use in the community has not been optimal, especially in the form of instant powder products that are more practical and have high economic value. This community service activity aims to empower women in RT 03 RW 01 Kubang Jaya Village, Siak Hulu, Kampar through training in the processing of red ginger instant powder. The implementation method includes socialization, demonstration, and direct practice, ranging from raw material preparation, extraction, cooking, sieving, to packaging and labeling. The results of the activity showed the high enthusiasm of the participants and the ability to produce instant ginger powder independently. This product is not only beneficial for health, but also has the potential to be developed as a household business to increase family income. This activity concluded that community empowerment through herbal processing training is effective in increasing knowledge, skills, and creativity while encouraging the use of local natural resources.